Systems Engineering: Design, Analysis, Programming, and Maintenance of Complex Systems (Industrial Engineering and Management, 2024)
System engineering is an interdisciplinary field where engineers, mathematicians, economists, scientists, and other experts can merge their abilities and skills to solve complex systems, dealing with design, analysis, programming, implementation, maintenance, and control. These complex systems can be tangible, such as high-voltage power systems, telecommunication infrastructure, or systems in the aerospace industry, or non-tangible, like computational systems, social environments, or economic problems. The solutions to these problems must ensure safety, reliability, efficiency, and maintainability. System engineering is a fascinating field because it is possible to have different visions for the same problem, providing part of the solution comes from other areas. The main idea is to assemble models (or several submodels) to represent an observed system, making it possible to study the various relationships within the system as well as those between the system and external agents. The division into submodels makes it possible to study each submodel’s performance in the system’s final result. Sometimes, small systems can also be complex due to the number of external agents interfering with the process or the number of observed variables. This book discusses applications of system engineering in different classes of problems and examines how a given solution for a specific problem can be transported and applied to solve another problem. It provides practical and theoretical explanations of problems, explores the application of system engineering tools, and describes the use of intelligent techniques.